(untitled) (Texas Journal of Philology, Culture and History, 2024)
This article describes the measures taken by the Soviet authorities in Uzbekistan in the field of preschool education on the basis of scientific, historical literature and sources. Also, the study included preschool education, children’s attendance and demographic indicators